Proceedings of the Analysis Conference, Singapore 1986 - Choy, Stephen T. L., 1937-; Jesudason, Judith P. (Judith Packer), 1956-; Lee, P. Y. (Peng Yee), 1938- (North-Holland mathematics studies, 1988)
The main emphasis of this volume is on harmonic and functional analysis. The papers include some of the latest research developments in this important field of mathematics.